Ideal for Whom? A Cultural Analysis of Ideal Worker Norms in Higher Education and Student Affairs Graduate Programs. Issue 176 (December 2016) - Sallee, Margaret W.
Abstract : This chapter explores the consequences of ideal worker norms for graduate student‐parents in higher education and student affairs programs. Using Schein's (2004) levels of culture as a conceptual lens, this chapter considers the ways that programmatic structures and interactions with faculty and peers reflect and reproduce a culture across graduate programs that privileges the norm of the always‐working and engaged student, thereby creating barriers to full participation for students with children.